The impact of digital interventions on stress levels in caregiver of people with mental disorders: A systematic literature review - Ima Safitri Puji Utami; Ahmad Yusuf; Rr Dian Tristiana (Program Studi Ilmu Keperawatan-fakultas Ilmu Kesehatan Universitas Malahayati, 2026)
Background: Informal caregivers of people with mental disorders (ODGJ) often experience complex and multidimensional burdens, including psychological stress, emotional exhaustion, and limited access to professional support. With technological advances, digital interventions have begun to be utilized as an innovative approach to alleviate caregiver burden. However, evidence regarding the effectiveness and characteristics of these interventions remains scattered and has not been systematically analyzed. Purpose: To systematically review and analyze the effectiveness and characteristics of digital interventions in alleviating the psychological burden of informal caregivers of people with mental disorders Method: A systematic review using PRISMA guidelines. Articles were searched using three databases: PubMed, ScienceDirect, and Scopus. A total of 332,609 articles were identified (PubMed n = 27,118; ScienceDirect n = 305,460; Scopus n = 31), then selected based on inclusion and exclusion criteria. The variables analyzed were digital interventions (web, mobile, or a combination) and caregiver psychological outcomes (stress, anxiety, and depression levels). The research instrument used the PICO framework. The analysis was conducted using thematic qualitative methods. Each article was assessed using the JBI critical appraisal tools. Results: Twelve articles met the inclusion criteria and were of good methodological quality. Results indicated that most digital interventions—whether mobile app-based, web-based, or telehealth-based—were effective in reducing caregiver stress, improving mental well-being, and enhancing caregiving skills. Technology-based interventions were generally well-received and considered practical and flexible, although not all were proven superior to traditional approaches. Conclusion: Digital interventions have a positive impact on caregivers of patients with mental illness in terms of psychological aspects and caregiving competency. Policy support and integration of digital services into the mental health system are important recommendations for the future.